The origins of perspective taking lie in iconic language use: Unifying theories of signs, conversation, and narrative perspective - Verhagen, Arie (Frontiers in Communication, 2023)
This paper proposes a theoretical reduction of the existence of perspective taking in discourse to the combination of two basic methods of communication: iconic simulation, and description by means of conventional symbols. This includes an integration of the depiction theory of quotation (Clark 2016) and a pragmatic version of the theory of signs (Keller 1998). Perspective taking is argued to be a consequence of the iconic simulation of acts, linguistic acts in particular. The basic fact that a single utterance can comprise both depictive and descriptive components is in turn the basis for the occurrence of different variants of speech and thought representation, which are traditionally discussed under the rubric of indirect and free indirect discourse. On this basis, it is argued that the phenomena can actually be analyzed more insightfully (and more simply) directly in terms of interactions between specific linguistic items and the distinction between depiction and description. In addition, this ‘composite utterance’ approach to perspective taking combines abstract conceptual clarity and simplicity with a high degree of flexibility in the way such interactions can work out in specific situations, which allows it to also serve as a basis for the analysis of ‘multiperspectival’ and ‘doublevoiced’ discourse.